Can Phillips Curve be applied in selected European countries today? - Aleksandra Živković (Anali Ekonomskog fakulteta u Subotici, 2023)
Phillips curve is one of the most important economic postulates, which indicates inversion between inflation rate and unemployment rate. Even though this has been empirically confirmed many times, in past research there have been evidence of rejecting Phillips curve in some countries. Aim of this research is to analyse does Phillips curve exists in selected European countries: Bulgaria, Greece, Slovenia and Romania, during time period Q1 2009 – Q3 2021. Panel analysis and choosing the appropriate model has led to the conclusion that there is a statistically significant inverse correlation between these two variables, which led to confirming existence of Phillips curve. These results are important indicator for policy makers, since inverse correlation between inflation rate and unemployment rate should highly be included when making decision for economic policy.